Parkinsonism and severe hypothyroidism in an elderly patient: a case of lithium toxicity due to pharmacological interactions. (12th April 2014) - Basile, G.; Epifanio, A.; Mandraffino, R.; Trifirò, G.
Summary What is known and objective Hypothyroidism is a common clinical side effect of lithium treatment, whereas parkinsonism is a very rare adverse event. A number of case series of clinical signs of reversible and permanent parkinsonism due to lithium toxicity have been previously published, but never in association with hypothyroidism. We describe a rare clinical case of concurrent reversible parkinsonism and severe hypothyroidism due to lithium toxicity. Case summary The patient was a 74‐year‐old woman chronically treated with carbonate lithium (300 mg, twice daily) and clomipramine (75 mg, once daily); she also received valsartan (160 mg) plus hydrochlorothiazide (12·5 mg), once daily. The patient was visited after a 1‐week history of progressively worsening and disabling parkinsonism. Laboratory tests showed elevated values of lithium and thyroid stimulating hormone (TSH) serum concentrations as well as reduced circulating thyroid hormone serum concentrations. Lithium treatment was discontinued; treatment with levothyroxine and saline solution i.v. was readily performed, and valsartan plus hydrochlorothiazide were replaced with amlodipine (5 mg, once daily). Within a few days, the patient showed a rapid improvement in overall clinical condition, but complete resolution of neurologic symptoms occurred only after about 5 months. What is new and conclusion Lithium toxicity may present with concurrent hypothyroidism and parkinsonism. In the present case, interaction with valsartan and hydrochlorothiazide most likely played an important role. In patients who receive chronic therapy with lithium, prescribers should monitor lithium serum concentration both periodically and immediately at the onset of signs and symptoms, potentially related to lithium toxicity.